Accounting and Finance: An Introduction - Eddie McLaney; Peter Atrill (United Kingdom Pearson, 2020)
Accounting and Finance: An Introduction, now in its eighth edition, contains all the information you need to start your business career. With its use of practical techniques and real-world examples, this best-selling text teaches you the basics of understanding and using financial information. This comprehensive guide covers financial accounting, management accounting and financial management in a single text, and provides you with the tools to make informed, successful business decisions. Key Features: *Up-to-date coverage, including the latest IFRSs and corporate governance content plus a discussion of financing and dividend policies ; *Accessible step-by-step approach helps you master the subject one step at a time; *New real world examples provide opportunities to apply and develop techniques; *Progress checks, activities and exercises reinforce learning; *Focus on decision-making prepares you for careers in business.
Keywords: Finance; Financial accounting; Accounting; Textbooks; The International Market Environment (ECO1021-N); (ACC1057-N) Business Finance